Effects of Glucose on the Reactive Black 5 (RB5) Decolorization by Two White Rot Basidiomycetes - Tony Hadibrata; Abdull Rahim Mohd Yusoff; Azmi Aris; Risky Ayu Kristanti; Topik Hidayat; Adhi Yuniarto (Institute for Research and Community Services (LPPM) ITB, 2011)
The capacities of glucose in the decolorization process of an azo dye, Reactive Black 5 (RB5), by two white rot basidiomycetes, Pleurotus sp. F019 and Trametes sp. F054 were investigated. The results indicated that the dye degradation by the two fungi was extremely correlated with the presence of glucose in the culture and the process of fungi growth. Decolorization of 200 mg dye/l was increased from 62% and 69% to 100% within 20